A Ação Popular (AP) no Movimento Estudantil Universitário de Passo Fundo entre a implantação da ditadura militar e o AI-5 - Oliveira, Nilton Cleber de (2014)
This dissertative work seeks to understand the process of acting group called the "Ação Popular" (Popular Action) (AP), the university student movement in the city of Passo Fundo during the civil-military dictatorship. The historical period chosen was the period between the years of 1964, the Civil-Military Coup in Brazil, and the year 1968, year of the Institutional Act No. 5, which ushered in the period of greatest repression of democratic freedoms within said dictatorship. This period is marked by the actual existence of a dictatorship with the limitations of freedoms of organization and even combat entities that opposed the regime deployed. However, the format of repression in the previous Institutional Act No. 5 period enabled the existence of actions and organizations within the student movement. After the AI- 5, there is a cut, mass mobilizations opposing the regime no longer exist. The university student movement is one of the most persecuted in the process. The central objective of this work is to understand the transformations of this group that undergoes profound changes in the organizational and ideological perspective. In organizational perspective becomes a bourgeois eclectic and small group and it turns into a revolutionary group inspired by Maoism. On the ideological aspect of a perspective fundamentally Christian action, undergoes transformations to adopt the Marxist theory of understanding the world. These changes occur in a period of profound political changes in Brazil. The country undergoes democratic regimes, where there was already an ideological intensification fueled by the Cold War, to a civilian-military coup and a subsequent coup within the coup inciting dictatorial practices after the AI- 5. Perceive the effects of these external and internal transformations between these young people entered higher and fresh education in Passo Fundo, dipped in disputes and tensions over its control. Forms of disputes in the student movement, their flags, their modes of action, their activities during this period were analyzed. We sought to determine the causes of the end of the People's Action in our city, what were the effects of the intensification of the repression of the student movement within the People's Action Step Fund. Finally, picked up the analysis that some of the leaders of the time made this period and its actions and judgments of these actions